Muted narratives of traumatic experiences of the Lithuanian Jewish women in the anti-Nazi Partisan Resistance - Latvytė, Neringa (Genocidas ir rezistencija, 2024)
This article is based on the international research project ‘Identity on the Line’, conducted by the Faculty of Communication of Vilnius University together with partners from Norway, Sweden, Denmark, Poland, Slovenia and Croatia memory institutions, from 2019 to 2023. The research undertaken by the Faculty of Communication deals with the traumatic experiences, wounded past and muted memories of women who survived the Holocaust and how these influenced the lives of their children and grandchildren, even when being kept silent. The article represents only part of the project and analysis of the traumatic experiences of the Jewish women who were fighting in the anti-Nazi partisan resistance by joining the combat units in the forests, as well as consequences and intergenerational transmission of a traumatic past.The purpose of this article is to show the muted stories of traumatic experiences, and how psychological scars of the war and the Holocaust are reflected in the daily life of women and their family members. What happens when the surrounding environment becomes dangerous and life-threatening? How does that challenge a person’s identity and narratives? How do these traumatic experiences affect the lives of the second and third generations in the family? This article tries to answer these complicated questions by interviewing Jewish women partisans, referring to their diaries, memoirs and testimonies as well as by interviewing the daughters of the survivors.
Keywords: Holocaust; silent memory; traumatic past; women; survivors; partisans; resist¬ance